Role of glucocorticoid receptor (GR) in white adipose tissue beiging - Martín, Florencia Magalí (2023)
Aim: Glucocorticoids (GCs) play a crucial role in energy homeostasis including white adipose tissue function; however, chronic GC excess is detrimental to mammals' health. White hypertrophic adiposity is a main factor for neuroendocrine-metabolic dysfunctions in monosodium L-glutamate (MSG)-damaged hypercorticosteronemic rat. Nevertheless, little is known about the receptor path in endogenous GC impact on white adipose tissue-resident precursor cells to bring them into beige lineage. Thus, our aim was to explore whether transient/chronic endogenous hypercorticosteronemia affects browning capacity in white adipose tissue pads from MSG rats during development. Main methods: Control and MSG male rats aged 30 and 90 days were 7-day exposed to cold conditions in order to stimulate wet white epidydimal adipose tissue (wEAT) beiging capacity. This procedure was also replicated in adrenalectomized rats. Key findings: Data indicated that whereas epidydimal white adipose tissue pads from prepubertal hypercorticosteronemic rats retained full expression of GR/MR genes resulting in a drastic reduction in wEAT beiging capacity, conversely, chronic hypercorticosteronemic adult MSG rats developed down-regulation of corticoid genes (and reduced GR cytosolic mediators) in wEAT pads and consequently partially restored local beiging capacity. Finally, wEAT pads from adrenalectomized rats revealed up-regulation of GR gene accompanied by full local beiging capacity. Significance: This study strongly supports a GR-dependent inhibitory effect of GC excess on white adipose tissue browning, an issue strongly supporting a key role of GR in the non-shivering thermogenic process. As a consequence, normalizing the GC milieu could be a relevant factor to handle dysmetabolism in white hyperadipose phenotypes.